1994
DOI: 10.1086/646811
|View full text |Cite
|
Sign up to set email alerts
|

Measles Immunity in a Population of Healthcare Workers

Abstract: A small but important proportion of healthcare workers are susceptible to measles. Whenever feasible, measles immunity programs for healthcare workers should include workers born before 1957. Of workers born after 1956, those from outside the United States are more likely to be immune than workers from inside the United States. Using the currently available vaccine, revaccination of initial non- or hyporesponders appears to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Although the numbers were too small for statistical comparison, we found a tendency for nonimmune health care workers to be young, which may reflect the low uptake of vaccine amongst this group and low exposure to measles. This has been observed in other studies [11,17]. Seroprevalence data for this age group [12] and the current age distribution of confirmed cases of measles support these observations.…”
Section: Discussionsupporting
confidence: 89%
“…Although the numbers were too small for statistical comparison, we found a tendency for nonimmune health care workers to be young, which may reflect the low uptake of vaccine amongst this group and low exposure to measles. This has been observed in other studies [11,17]. Seroprevalence data for this age group [12] and the current age distribution of confirmed cases of measles support these observations.…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of seronegative personnel was dependent on age, with older healthcare personnel more likely to have had natural infection and, therefore, higher measles seroprevalence [17, 84, 8789, 92, 93, 95]. Two studies from the post-elimination era conducted in 2008 and 2009 reported that among the subset of healthcare personnel without documentation of measles immunity who had serologic testing done, 9% and 11.6% lacked measles antibodies [18, 97].…”
Section: Resultsmentioning
confidence: 99%
“…Not all healthcare personnel require measles vaccine; many may have naturally acquired immunity, especially older healthcare personnel and those from countries where measles remains endemic [17, 47, 84, 8789, 92, 93, 95]. Evidence of measles immunity is also essential for interpreting data on measles vaccine coverage among healthcare personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Because most HCWs have natural or acquired immunity to these viruses, only immune personnel generally care for patients with these infections. [773][774][775][776] Although there is no evidence suggesting that masks are not adequate to protect HCWs in these settings, for purposes of consistency and simplicity, or because of difficulties in ascertaining immunity, some facilities may require the use of respirators for entry into all AIIRs, regardless of the specific infectious agent present.…”
Section: Iie Personal Protective Equipment For Health Care Workersmentioning
confidence: 99%